"We also deserve help during the pandemic": The effect of the COVID-19 pandemic on foreign domestic workers in Hong Kong - Ingrid D. Lui; Nimisha Vandan; Sara E. Davies; Sophie Harman; Rosemary Morgan; Julia Smith; Clare Wenham; Karen Ann Grépin (Elsevier, 2021)
The coronavirus disease 2019 (COVID-19) pandemic poses particular challenges for migrant workers around the world. This study explores the unique experiences of foreign domestic workers (FDWs) in Hong Kong, and how COVID-19 impacted their health and economic wellbeing. Interviews with FDWs (n = 15) and key informants (n = 3) were conducted between May and August 2020. FDWs reported a dual-country experience of the pandemic, where they expressed concerns about local transmission risks as well as worries about their family members in their home country. Changes to their current work situation included how their employers treated them, as well as their employment status. FDWs also cited blind spots in the Hong Kong policy response that also affected their experience of the pandemic, including a lack of support from the Hong Kong government. Additional support is needed to mitigate the particularly negative effects of the pandemic on FDWs.